2022
DOI: 10.1101/2022.05.18.22275272
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Population health impact, cost-effectiveness, and affordability of community-based HIV treatment and monitoring in South Africa: a health economics modelling study

Abstract: IntroductionCommunity-based delivery and monitoring of antiretroviral therapy (ART) for HIV has the potential to increase viral suppression for individual- and population-level health benefits. However, the cost-effectiveness and budget impact are needed for public health policy.Methods and FindingsWe used a mathematical model of HIV transmission in KwaZulu-Natal, South Africa, to estimate population prevalence, incidence, mortality, and disability-adjusted life-years (DALYs) from 2020 to 2060 for two scenario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…TPT uptake was higher among participants who received community‐based care [ 19 ]. A recent modelling analysis concluded that community‐based HIV treatment was cost‐effective in preventing death and disability due to HIV [ 20 ]. However, the impacts of increased ART and TPT uptake on incident TB and TB deaths were not quantified among trial participants, nor among the surrounding community.…”
Section: Introductionmentioning
confidence: 99%
“…TPT uptake was higher among participants who received community‐based care [ 19 ]. A recent modelling analysis concluded that community‐based HIV treatment was cost‐effective in preventing death and disability due to HIV [ 20 ]. However, the impacts of increased ART and TPT uptake on incident TB and TB deaths were not quantified among trial participants, nor among the surrounding community.…”
Section: Introductionmentioning
confidence: 99%
“…TPT uptake was higher among participants who received community-based care than participants who received facility-based care [19]. A recent modelling analysis concluded that community-based HIV treatment was cost-effective in preventing death and disability due to HIV [20]. However, the longer-term impact of increased ART and TPT uptake on incident TB and TB deaths were not quantified among trial participants, nor were TB incidence or deaths quantified among community members who were not in the trial.…”
Section: Introductionmentioning
confidence: 99%